h - Stephanidis, Constantine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This two-volume set CCIS 173 and CCIS 174 constitutes the extended abstracts of the posters presented during the 14th International Conference on Human-Computer Interaction, HCII 2011, held in Orlando, FL, USA in July 2011, jointly with 12 other thematically similar conferences. A total of 4039 contributions was submitted to HCII 2011, of which 232 poster papers were carefully reviewed and selected for presentation as extended abstracts in the two volumes.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; Software Engineering